IMPLEMENTASI MEDIA GAMBAR BERBASIS POWERPOINT UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DI SMP NEGERI 1 TILONGKABILA - Gusasi, Dewita; Zakaria, Perry; Yahya, Lailany (Universitas Islam Sumatera Utara, 2025)
This study aims to implement PowerPoint-based image media to improve students' mathematical problem-solving skills. The subjects of this study were 30 students in class VII-2 of SMP Negeri 1 Tilongkabila, consisting of 12 boys and 18 girls. The research instrument was the results of the students' scores on a mathematical problem-solving test on data and diagrams. The data analysis techniques in this study were teacher observation, student observation, and mathematical problem-solving ability tests. This study used the action research method, with research procedures including planning, action, observation, and reflection. The research consisted of two cycles. The results of the research in cycle I showed that the results of observations of teacher activities only reached 66.67%, and student activities 58.33% with good criteria, and the level of students' mathematical problem-solving skills that were complete was only 14 students or 46.67%, while there were 16 students or 58.33% who were not yet complete. Because the success indicator of at least 80% was not achieved, the research continued to cycle II. In cycle II, the results of observations of teacher activities were 94.45% and student activities were 88.89% with good and very good criteria, and the level of students' mathematical problem-solving skills was 26 students or 86.67%. It is concluded that the implementation of PowerPoint-based image media can improve students' mathematical problem-solving skills.